2020
DOI: 10.1007/s12282-020-01137-5
|View full text |Cite
|
Sign up to set email alerts
|

Awake breast cancer surgery: strategy in the beginning of COVID-19 emergency

Abstract: Introduction COVID-19 is a declared worldwide pandemic. In our country, due to shortage of hospitals and beds in intensive care unit, oncological and breast cancer (BC) resources are temporarily shifted to COVID-19 patients. In addition, risk of cross-infections should be considered in these frail patients. To accomplish more surgical procedures and to reduce the length of hospital stay (LOS), fast track awake BC surgery should be implemented. The aim of the study is to estimate the effects of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 32 publications
5
40
0
Order By: Relevance
“…Although breast cancer is the most frequent cancer and represents the leading cause of oncological death among women worldwide; latest statistics suggest that there has been an improvement in term of prognosis (14,15). Both, empowerment of breast cancer treatments and higher incidence of early diagnosis, due to the screening, have led to this improvement (9)(10)(11)(12)(13)(14)(15)(16). The benefits of screening are largely attributed to the ability to diagnose breast cancer in earlier stages (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although breast cancer is the most frequent cancer and represents the leading cause of oncological death among women worldwide; latest statistics suggest that there has been an improvement in term of prognosis (14,15). Both, empowerment of breast cancer treatments and higher incidence of early diagnosis, due to the screening, have led to this improvement (9)(10)(11)(12)(13)(14)(15)(16). The benefits of screening are largely attributed to the ability to diagnose breast cancer in earlier stages (17).…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have reported that in addition to the improvement in survival, there is a significant reduction in breast cancer diagnosed by physical examination (e.g. palpable lesion) (7,(10)(11)(12). We hypothesized that screening suspension and surgical treatment delay could alter the clinical presentation and features of breast cancer.…”
mentioning
confidence: 97%
“…Some reports have indicated that breast reconstruction during the COVID-19 pandemic was limited to immediate tissue expander insertion and silicone breast implant replacement only [ 3 , 4 ]. Avoiding autologous tissue reconstruction reduces the operation time and hospital stay, and awake surgery has been reported as a method to reduce the operation time [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have introduced the concept of awake breast surgery during the COVID-19 pandemic as a means of reducing the incidence of viral infection and maximizing the utility of hospital service during a period of intense pressure ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our report ( 11 ), financial analysis of awake breast surgery would be beneficial to help improve the current model of care for patients with breast cancer that require wide local excision.…”
Section: Introductionmentioning
confidence: 99%